Main causes of condemnation of pork carcasses in refrigerators, under the screening of the state inspection service, in the municipality of Ji-Paraná – RO (Research, Society and Development, 2022)
Pig farming is one of the branches within livestock that has shown excellent financial results. In the animal protein market, pork is the most consumed meat around the world and Brazil has occupied fourth place in the world ranking. Given this importance, it is essential that the slaughter production processes follow standardized steps and ensure the production of good quality carcasses. In this sense, swine have been increasingly subjected to intensive rearing conditions, in which the slightest failure, during the process, can cause damage to the production chain. In addition, respiratory pathologies are the major cause of losses in slaughterhouse/refrigerator, thus compromising the final product. In view of this, the present work aims to evaluate the main causes of condemnation of the carcass of slaughtered pigs, in a slaughterhouse, located in the municipality of Ji-Paraná, Rondônia, under the scrutiny of the state inspection service. For the collection of information, it was sought in the post-mortem inspection reports of swine slaughter, from a slaughterhouse, through nosographic data, and using a methodology of a quantitative/descriptive/documentary nature, the data were analyzed and demonstrated that, the main causes of condemnation of carcasses, followed, as a result of respiratory pathologies, highlighting the purulent adherence of the pleura and Multiple lung abscesses.